2015
DOI: 10.1111/jace.13534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stoichiometry on Structural and Optical Properties of Sputter Deposited Multicomponent Tellurite Glass Films

Abstract: Multicomponent TeO 2 -Bi 2 O 3 -ZnO (TBZ) glass thin films were prepared using RF magnetron sputtering under different oxygen flow rates. The influences of oxygen flow rate on the structural and optical properties of the resulting thin films were investigated. We observed that thin films sputtered in an oxygen-rich environment are optically transparent while those sputtered in an oxygen-deficient environment exhibit broadband absorption. The structural origin of the optical property variation was studied using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
(85 reference statements)
4
8
0
Order By: Relevance
“…Figure 7B presents the high‐resolution scan and the fitted peak for Te3d spectra. The peaks at 586.4 and 576.3 eV, respectively, corresponding to the doublets Te3d 3/2 and Te3d 5/2 were observed, according to the report for amorphous TeO 2 50 . The Te3d 5/2 peak of the examined glass is deconvoluted into two peaks contributed at 575.0 and 576.3 eV.…”
Section: Resultssupporting
confidence: 72%
“…Figure 7B presents the high‐resolution scan and the fitted peak for Te3d spectra. The peaks at 586.4 and 576.3 eV, respectively, corresponding to the doublets Te3d 3/2 and Te3d 5/2 were observed, according to the report for amorphous TeO 2 50 . The Te3d 5/2 peak of the examined glass is deconvoluted into two peaks contributed at 575.0 and 576.3 eV.…”
Section: Resultssupporting
confidence: 72%
“…Based upon previous observations for other tellurite-based glass lms 42 and bulk tellurite glass, 43 this color appearance is attributed to the presence of reduced tellurium species or metallic-Te. 30,35,42 In order to eliminate the undesired color via oxidization of the metallic-Te in the lm, higher xerogel heating temperatures of 400 C and 500 C were applied. The increased xerogel heating temperatures successfully eliminated the brown color but led to white and opaque appearance ( Fig.…”
Section: Impact Of Sol Heating and Xerogel Heating On Metallic-te Andsupporting
confidence: 58%
“…Bismuth zinc tellurite Radio Frequency (RF) magnetron reactive sputtered glass films were synthesized aiming to improve the optical transmission in the visible range [ 8 ]. It was demonstrated that the O 2 purge into Ar working gas improved the optical transparence of the films in the visible domain by suppressing the reduction process of TeO 2 into metallic-Te atoms.…”
Section: Introductionmentioning
confidence: 99%